Sequential Conia-ene-type cyclization and Negishi coupling by cooperative functions of B(C6F5)3, ZnI2, Pd(PPh3)4 and an amine. Issue 36 (11th September 2020) - Cao, Min; Yesilcimen, Ahmet; Prasad, Soumil; Genova, Jason; Myers, Tanner; Wasa, Masayuki
Abstract : A hybrid catalyst system for sequential Conia-ene-type cyclization/Negishi coupling for union of alkynyl ketones and aryl iodides has been developed. Abstract : We disclose a method for sequential Conia-ene-type cyclization/Negishi coupling for the union of alkynyl ketones and aryl iodides. This process is promoted through cooperative actions of Lewis acidic B(C6 F5 )3, ZnI2, Pd-based complex, and a Brønsted basic amine. The three Lewis acid catalysts with potential overlapping functions play their independent roles as activators of carbonyl group, alkyne moiety, and alkenyl zinc intermediate, respectively. A variety of 1, 2, 3-substituted cyclopentenes can be synthesized with high efficiency.